Body fat in the elderly: comparison between anthropometrics, electrical bioimpedance and predictive equations in the elderly (Research, Society and Development, 2022)
To compare the values of body fat (BC) obtained by anthropometry with bioimpedance (BIA) and with different predictive equations in the elderly. This is a cross-sectional study carried out with elderly users of health and social care services in Lagarto, Sergipe. The anthropometric measurements evaluated were weight, height and skinfold thickness. The GC was determined through the equation proposed by Durnin & Womersey (1974) to determine the percentage of GC (%GC). The bioimpedance test was performed using the Biodynamics 450® and five predictive equations existing in the literature were evaluated. The sample consisted of 63 elderly people, with a mean age of 67.9±5.7. There was a difference between the means of Anthro% GC, MLGBIA and %GCBIA between the sexes, with GC being superior among women (p